4 - Julius Nyerere et la révolution africaine - Harry GOULBOURNE (Africa Development, 1982)
In this article the author looks into NYERERE's contribution to the liberation of Africa . According to the author, NYERERE contributed not only as a Leader of a political party and a Head of State but also as result of his strong commitment to the cause of panafricanism. The author analyses NYERERE's conception of liberation , his involvement in the liberation struggle of South Africa and his conception of socialism vis-à-the African Revolution . Concerning NYERERE's conception of Liberation , the author quotes his definition which says that «liberation is a historical process but not a unique action whose achievement is celebrated every year». Four steps characterize this process: liberation from the colonial power from racial minority ; liberation from the domination of the economy foreien powers ; liberation from poverty , injustice and oppression imposed on Africans by Africans ; liberation from the spiritual principle which makes Africans think that they are inherently inferior to other peoples. This conception of liberation continously permeates his political actions especially when it comes to getting Tanzania and himself involved in the liberation of South Africa. This is perhaps the area in which differs śtenificantly from most other African Leaders because he never separated the Tanzanian reality as a dominated country from the liberation of the continent. As a result of this relationship , the author says NYERERE's conception of socialism vis-à-vis the African Revolution one that advocates a necessary relation between these two concepts. Ample evidence of that cait be found in almost all his writings. Harry GOULBOURNE, Maître de Conférence, Département de Sciences Politiques, Université des Antilles - Kingston, Jamaïque. Article présenté à ia Vie Conférence bis-annuelle de l'Association Africaine de Science Politique, Harare, Zimbabwe, 23-27 Mai 1981.